MULŢIMI DE ECHILIBRE STACKELBERG ÎN JOCURILE DIADICE ÎN STRATEGII MIXTE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2010)
We consider the problem of determining the set of Stackelberg equilibria for dyadic games in mixed strategies. We propose an algorithm for determining the Stackelberg equilibria in dyadic games.The main results are formulated and explained. A procedure for the equilibrium set determining is presented. It is applied to solve illustration examples.